2017
DOI: 10.1155/2017/9786972
|View full text |Cite
|
Sign up to set email alerts
|

Chinese Herbal Formula, Modified Danggui Buxue Tang, Attenuates Apoptosis of Hematopoietic Stem Cells in Immune-Mediated Aplastic Anemia Mouse Model

Abstract: A derivative formula, DGBX, which is composed of three herbs (Radix astragali, Radix Angelicae sinensis, and Coptis chinensis Franch), is derived from a famous Chinese herbal formula, Danggui Buxue Tang (DBT) (Radix astragali and Radix Angelicae sinensis). We aimed to investigate the effects of DGBX on the regulation of the balance between proliferation and apoptosis of hematopoietic stem cells (HSCs) due to the aberrant immune response in a mouse model of aplastic anemia (AA). Cyclosporine (CsA), an immunosup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…The constituents of Coptis chinensis were analyzed by HPLC-ESI/MS n . The specific measurement procedures referred to our previous works methods as previously described [ 12 14 ]. Peak View Software 2.2 was used to analyze the data, including retention time, accurate mass and MS/MS spectrum comparison.…”
Section: Methodsmentioning
confidence: 99%
“…The constituents of Coptis chinensis were analyzed by HPLC-ESI/MS n . The specific measurement procedures referred to our previous works methods as previously described [ 12 14 ]. Peak View Software 2.2 was used to analyze the data, including retention time, accurate mass and MS/MS spectrum comparison.…”
Section: Methodsmentioning
confidence: 99%
“…EMSA eritin, a polyherbal formulation had increased proliferation of HSC in irradiated BALB/c mice in vivo and triggered differentiation into the lymphopoiesis lineages [40]. Inducing of proliferation and attenuating of apoptosis were observed when an immune-mediated aplastic anaemia mouse model was treated with a modified Chinese herbal formula prepared with Radix astragali, Radix Angelicae sinensis and Coptis chinensis Franch [41].…”
Section: Effects Of Herbal Extracts On Human Stem Cells 21 Stimulatmentioning
confidence: 99%
“…Our previous studies have verified the hematopoietic function of modified DBT in anaplastic anemia mouse model by bone marrow suppression. The results indicated that modified DBT could decrease the proliferation and differentiation of effector T cells, impair Treg-mediated immunosuppressive functions, attenuate immune-mediated destruction of HSCs, repair hematopoietic failure and recover the hematopoietic function of HSCs in vivo [18,19].…”
Section: Introductionmentioning
confidence: 99%